Pengaruh Tingkat Inflasi, Nilai Tukar (Kurs), Tingkat Suku Bunga Dan Jumlah Uang Beredar Terhadap Indeks Harga Saham Gabungan (IHSG)(Studi Pada Bursa Efek Indonesia Periode 2012-2016)SKRIPSI - Efendy Kurniawan, Decky, Dra. Wuryaningsih DL., MM (2017)
This study aimed to obtain evidence about the effect of inflation, the exchange rate, interest rates and money supply on Stock Price Index (CSPI) in Indonesia Stock Exchange (IDX). The period used in this study five (5) years, starting out from 2012 to 2016. The analytical method used in this research is the method of multiple linear regression analysis was performed with SPSS 15 with level of significant at 0,05. Before the test multiple linear regression analysis performed classical assumption in advance so that the resulting regression equation is BLUE (Best, Linear, Unbiased, Estimator). The data used is secondary data in the form of time series such as monthly data from the years 2012-2016 for each of the study variables. In addition to assessing the goodness of fit model t test, F test and coefficient of determination. Based on the analysis concluded that the level of inflation and interest rates do not affect the CSPI. While the exchange rate negatively affect on Composite Stock Price Index (CSPI), as well as the money supply has positive effects on the Composite Stock Price Index (CSPI). Taken together 2 (simultaneously) the inflation rate, exchange rate, interest rate and money supply affect on the Composite Stock Price Index (CSPI).